Nunney Castle
In addition to the growing unrest at home from the aftereffects of the plague, the Court , headed by King Edward III, initiated the Hundred Years' War with France, in what was felt to be a return to chivalry and feats of arms. His son the Black Prince, won his Spurs at Poitiers and there were notable victories at Crecy. Nunney Castle, built by John de la More on his successful return from the war, was planned on similar lines to castles hen being built on the Continent against the English. A smaller and simpler version of the great Welsh fortresses, it nevertheless indicated an unease similar to that of the bishops.